1994
DOI: 10.1111/j.1365-3083.1994.tb03392.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of T Lymphocytes in Experimental Staphylococcus aureus Arthritis

Abstract: Using a recently developed murine model of haematogenously induced Staphylococcus aureus, the authors have characterized the phenotypes and functional properties of inflammatory cells present in the synovium of arthritic mice. The results show that large numbers of granulocytes and macrophages were observed in the inflamed synovia within 24 h of inoculation of S. aureus strain LS-1. Many of the synovial macrophage-like cells strained for cytoplasmic IL-1 alpha and TNF-alpha. Subsequently (> or = 48 h later), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 33 publications
3
49
0
Order By: Relevance
“…Earlier studies have demonstrated the pivotal role of CD4 þ T cells in the progression of septic arthritis [8,9]. In the light of a recent report demonstrating that NK cells can play an important role in down-regulating Th1-mediated experimental colitis by controlling the responses of effector T cells to gut bacteria [28], we analysed the effect of in vivo NK cell depletion on T celldependent inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies have demonstrated the pivotal role of CD4 þ T cells in the progression of septic arthritis [8,9]. In the light of a recent report demonstrating that NK cells can play an important role in down-regulating Th1-mediated experimental colitis by controlling the responses of effector T cells to gut bacteria [28], we analysed the effect of in vivo NK cell depletion on T celldependent inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…The role of lymphocytes in disease development has been extensively studied. Abdelnour et al have shown that T lymphocytes play a major pathogenic role in the disease [8,9]. Also, B lymphocytes contribute to arthritis, as shown in studies demonstrating that B cell-deficient Xid mice display a less severe arthritis [10].…”
Section: Introductionmentioning
confidence: 99%
“…This could be due to the down-regulation of polyclonal B cell activation as well as T cell activities [41,42]. In this context, B [30] and T cells [3,4] contribute to the progression of septic arthritis. Such effects were, however, not observed when naive (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…05). In order to check the efficiency of L-NMMA in inhibiting NO synthase, the serum levels of NO 3 ¹ , a stable metabolite of NO, were determined and proved to be significantly decreased in mice treated with L-NMMA compared with controls (70 . 1 Ϯ 7 .…”
Section: Effect Of L-nmma On the T Cell-dependent And Granulocytedepementioning
confidence: 99%
See 1 more Smart Citation